Empowering the Next Generation of Entrepreneurs: The Role of Innovation and Incubation Centres - Ravichandran, Ramasamy; Dixit, Preeti (Journal of Vocational Education Studies, 2024)
This study examines the critical role of incubation centers in empowering the next generation of entrepreneurs and contributing to the growth of economies worldwide. It explores the importance of incubation centers and highlights the crucial role of incubation centers in fostering entrepreneurship by providing resources, mentorship, and support to startups. The analysis of 26 peer-reviewed articles reveals consistent evidence of the positive impact of incubation centers on entrepreneurship development. Key findings include the ability of incubators to provide access to resources, facilitate knowledge sharing, and create supportive environments for startups to thrive. The study further presents data from surveys conducted with students and entrepreneurs engaged with incubation centers. Findings highlight the positive perception of incubation centers, with entrepreneurs reporting significant improvement in skills, access to valuable networks, and increased chances of success. The study further identifies challenges faced by incubation centers, such as lack of sustainable funding, bureaucratic hurdles, and limitations in selection processes. It proposes solutions like diversified funding models, streamlined administrative procedures, and focus on inclusivity to overcome these challenges. The study emphasizes the importance of creating a supportive ecosystem for startups, with incubation centers playing a key role in fostering collaboration and knowledge sharing. It suggests measures like creating vibrant communities, promoting entrepreneurial mindset, and nurturing innovation to empower the next generation of entrepreneurs. The study highlights the need for further research and strategic interventions to optimize the effectiveness of these centers and empower future generations of entrepreneurs.